A comprehensive analysis of six forms of cytochrome P450 2C (CYP2C) in pigs. (2nd November 2022) - Uno, Yasuhiro; Morikuni, Saho; Shiraishi, Mitsuya; Asano, Atsushi; Kawaguchi, Hiroaki; Murayama, Norie; Yamazaki, Hiroshi
Abstract: Pigs are an important species used in drug metabolism studies; however, the cytochromes P450 (P450s or CYPs) have not been fully investigated in pigs. In this study, pig CYP2C32, CYP2C33, CYP2C34, CYP2C36, CYP2C42, and CYP2C49 cDNAs were isolated and found to contain open reading frames of 490 or 494 amino acids that shared 64–82% sequence identity with human CYP2C8/9/18/19. Pig CYP2C genes formed a gene cluster in a genomic region that corresponded to that of the human CYP2C cluster; an additional gene cluster was formed by pig CYP2C33a and CYP2C33b distant from the first cluster but located in the same chromosome. Among the tissues analysed, these pig CYP2C mRNAs were preferentially expressed in liver, small intestine, and/or kidney; pig CYP2C49, CYP2C32, CYP2C34, and CYP2C33 mRNAs were the most abundant CYP2C mRNAs in liver, jejunum, ileum, and kidney, respectively. Metabolic assays showed that pig CYP2C proteins (heterologously expressed in Escherichia coli ) metabolised typical human CYP2C substrates diclofenac, warfarin, and/or omeprazole. The results suggest that these pig CYP2Cs are functional enzymes able to metabolise human CYP2C substrates in liver and small intestine, just as human CYP2Cs do.